Aplikasi, Pembelajaran, Siswa PEMANFAATAN APLIKASI PEMBELAJARAN PADA SMP YP HKBP 1 PEMATANGSIANTAR UNTUK MENINGKATKAN KEMAMPUAN PARA SISWA: PEMANFAATAN APLIKASI PEMBELAJARAN PADA SMP YP HKBP 1 PEMATANGSIANTAR UNTUK MENINGKATKAN KEMAMPUAN PARA SISWA - Peniel Sam Putra Sitorus; Jaya Tata Hardinata; Reagan Surbakti Saragih; Dudes Manalu; Ferri Ojak Immanuel Pardede (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
SMP YP HKBP 1 Pematangsiantar School is currently conducting face-to-face learning in class. The learning process is carried out by the teacher explaining in front of the class and writing the material given on the board and then the students note it down in a notebook to read again at home. However, not all students want to re-read the notes they have taken at home, but the grades given by the teacher to the students are less than satisfactory. Children now have gone through a health emergency and still like to read using digital information technology. The development of information technology means that information can be conveyed very quickly in all fields, including education. During a global disaster emergency several years ago, information technology was really needed to get the latest information. In the field of education, distance information technology is used to support learning. Education practitioners in Indonesia must learn again to use information technology in applications that are very developed and require the name of the internet. The internet makes it easier for people to get information quickly and affordably. In the field of education, the internet provides global access to information. There are various educational applications in the learning process, one of which is Padlet. The padlet application can be used by SMP YP HKBP 1 Pematangsiantar School to improve the abilities of SMP YP HKBP 1 Pematangsiantar School students in the learning process which interacts between teachers and students over long or near distances. Therefore, this service is carried out to improve the abilities of SMP YP HKBP 1 Pematangsiantar School students by using the Padlet application.